2016
DOI: 10.1186/s12864-016-3078-3
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association and replication study of anti-tuberculosis drugs-induced liver toxicity

Abstract: BackgroundDrug-induced liver injury (DILI) is a well-recognized adverse event of anti tuberculosis drugs (ATD) possibly associated with genetic variations. The objective of this study was to perform genome-wide association study (GWAS) to identify genetic variants associated with the risk for ATD induced liver toxicity in Ethiopian patients.ResultTreatment-naïve newly diagnosed tuberculosis patients (n = 646) were enrolled prospectively and treated with rifampicin based short course anti-tuberculosis therapy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 45 publications
3
28
0
Order By: Relevance
“…In addition, variants in AGBL4 and FAM65B were identified as potential risk factors for ATDinduced liver toxicity through GWAS (Petros et al, 2016). In the current study, we did not find genetic variants that passed genome-wide significance level in both the pharmacokineticrelated genes and HLA region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, variants in AGBL4 and FAM65B were identified as potential risk factors for ATDinduced liver toxicity through GWAS (Petros et al, 2016). In the current study, we did not find genetic variants that passed genome-wide significance level in both the pharmacokineticrelated genes and HLA region.…”
Section: Discussionmentioning
confidence: 99%
“…Genomewide association studies (GWAS) have identified variant alleles that are associated with an increased risk of developing DIH after treatment intentions with various classes of drugs (Aithal and Grove, 2015;Daly et al, 2009;Urban et al, 2014). Recently, using GWAS in Ethiopian TB patients, we have reported genetic variations in ATP-/GTP-binding proteinlike-4 (AGBL4) and family with sequence similarity 65 member-B (FAM65B) as potential risk factors for developing ATD-induced liver toxicity (Petros et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…FAM65B is expressed in the hepatocytes, gall bladder, and bile duct, and a recent study indicated that FAM65B plays roles in liver inflammation (Stoyanov et al, 2015). The GWAS on the antituberculosis drug-induced liver injury also identified a cluster of SNPs in the intron of ATP/GTP-binding protein-like 4 (AGBL4) suggestive of genome-wide significant association (Petros et al, 2016). Although further analysis is required to clarify the functional importance of FAM65B and AGBL4, the study demonstrated the potential of GWASs to discover genetic risk factors that mediate DIH due to antituberculosis drugs.…”
Section: Antituberculosis Drug-induced Hepatotoxicitymentioning
confidence: 99%
“…To date, a few GWASs have investigated genetic associations with idiosyncratic DIH (Cao et al, 2015;Kindmark et al, 2008;Lucena et al, 2011;Parham et al, 2016;Petros et al, 2016;Singer et al, 2010;Spraggs et al, 2011;Urban et al, 2012). The top associated SNPs are summarized in Table 1.…”
Section: Analysis Of the Topline Findingsmentioning
confidence: 99%
See 1 more Smart Citation